Characterizing cognitive aging of working memory and executive function in animal models - Bizon, Jennifer L.; Foster, Thomas C.; Alexander, Gene E.; Glisky, Elizabeth L. (Frontiers in Aging Neuroscience, 2012)
Executive functions supported by prefrontal cortical systems provide essential control and planning mechanisms to guide goal-directed behavior. As such, age-related alterations in executive functions can mediate profound and widespread deficits on a diverse array of neurocognitive processes. Many of the critical neuroanatomical and functional characteristics of prefrontal cortex are preserved in rodents, allowing for meaningful cross-species comparisons relevant to the study of cognitive aging. In particular, as rodents lend themselves to genetic, cellular and biochemical approaches, rodent models of executive function stand to significantly contribute to our understanding of the critical neurobiological mechanisms that mediate decline of executive processes across the lifespan. Moreover, rodent analogues of executive functions that decline in human aging represent an essential component of a targeted, rational approach for developing and testing effective treatment and prevention therapies for age-related cognitive decline. This paper reviews behavioral approaches used to study executive function in rodents, with a focus on those assays that share a foundation in the psychological and neuroanatomical constructs important for human aging. A particular emphasis is placed on behavioral approaches used to assess working memory and cognitive flexibility, which are sensitive to decline with age across species and for which strong rodent models currently exist. In addition, other approaches in rodent behavior that have potential for providing analogues to functions that reliably decline to human aging (e.g., information processing speed) are discussed.